Evaluation of learning in chemistry, physics and mathematics disciplines: An analysis of theory and practice in the classroom - Calera, Naiana; Simonato, Rosecleia Moraes; de Oliveira, Arquimar Barbosa; de Barba, Clarides Henrich [UNESP]; da Silva, Marinaldo Felipe (My University, 2018)
The research object of this study was to adapt existing didactic models to the new curricular requirements. We bring references that guide learning and evaluation in the different areas of the curriculum, showing a critical analysis regarding the evaluation of learning in the official documents and the reality in the school. When analyzing the proposed theories about the evaluation of learning in the current official documents, we find a mismatch with the practice, which emphasizes the traditional attitude of most science teachers.

O objeto de pesquisa deste trabalho, foiadequar os modelos didáticos existentes as novas exigências curriculares.Trazemos referências que direcionamo aprendizado e a avaliação nas diferentes áreas do currículo, mostrando uma análise crítica com relação a avalição da aprendizagem nos documentos oficiais ea realidade na escola. Ao analisarmos as teorias propostas sobre a avaliação da aprendizagem nos documentos oficiais vigentes, verificamos um descompasso com a prática, o qual ressaltamos a postura tradicional da maioria dos professores das ciências.
Avaliação da aprendizagem nas disciplinas de química, física e matemática: Uma análise da teoria e prática em sala de aula
Keywords: Avaliação da aprendizagem; Curriculum; Currículo; Evaluation of learning; Teoria e prática; Theory and practice